Primary Fallopian Tube Carcinoma : A Case Report - Rijalul Abrar; Syamel Muhammad (Universitas Andalas, 2021)
Objective: To report the case of primary fallopian tube carcinoma metastatic to cervix and omentum, but not infiltrate the ovariumMethod: Case Report Case: A 40 years old woman presented with gradual onset pain and swelling of the abdomen. The patient was diagnosed with suspected ovarian carcinoma. After examination, the patient prepared for laparotomy; salpingo-oophorectomy, omentectomy, mass resection from pelvic and rectum Result: The hystological examination result was high grade serous carcinoma from the fallopian tube metastasis to cavum douglas and omentum. This case is a rare case because the tubal carcinoma was metastasis to cavum douglas and omentum without infiltrate the ovarium.Discussion: Primary carcinoma of the fallopian tube is rare and accounts for about 0.14-1.8% of all gynecological malignancies. Clinically the diagnose of tubal carcinoma very similar to ovarian cancer, the diagnose can not distinguished pre operative. The new staging of FIGO may be reference for diagnostic and treatment of the desease. Thorough staging laparotomy is an important part of early management and systemic treatment. Keywords: tubal carcinoma, PFTC, metastasis, high grade serous carcinoma